Offshore companies as non-state actors of World Politics - I. V. Krasavin (Vestnik MGIMO-Universiteta, 2013)
Different types of non-governmental financial organizations influence onto states and world politics is being investigated in the article. Structure of contemporary international financial systems is shown and specificity of their influence onto real sector and state policy is explained. Special attention is aimed at offshores role in financial system and world politics.